The Outlook of Akhism to the Economic Life and Its Comparison with Capitalist System - Metin Ozdemir (International Journal of Science and Society, 2020)
The fact that human beings, the exceptional beings of the world, can maintain their vitality in trust and prosperity is depended on its success in production to meet its own needs, which is largely expressed as economics, and its justice-based behavior in consumption and sharing. In this sense, it is clearly not possible to realize the welfare and happiness of the world with the capitalistic system containing Neo-Liberal politics, which takes the sole purpose of capital accumulation by maximizing profits without any ethical anxiety. However, this capitalistic system is still being implemented as an economic system without an alternative in the majority of the World. On the other hand, in the Akhism whose the basic principles are the Islamic values, it is possible to see that much more reasonable principles are adopted both in the name of general welfare and peace of mankind, and also in the sense of sensitivity to the environment. In this work, both systems will be compared in order to promote the foundation of world peace and the general prosperity of humanity.